EKSISTENSI PARIWISATA BUDAYA BALI DALAM KONSEP TRI HITAKARANA - I Gusti Agung Made Gede Mudana (Institut Pariwisata dan Bisnis Internasional, 2018)
The success of Bali tourism has become a legend both nationally and internationally. Bali Island is known as one of the best tourist islands in the world. Various awards were obtained by Bali Island as the best island and the most favorite place to travel throughout the world. Bali is the